DEVELOPING ELECTRONIC STUDENT WORKSHEET (E-WORKSHEET) BASED PROJECT USING FLIPHTML5 TO STIMULATE SCIENCE PROCESS SKILLS DURING THE COVID-19 PANDEMIC - Ferdi Febriansyah; Kartini Herlina; I Dewa Putu Nyeneng; Abdurrahman Abdurrahman (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
This research aims to develop worthy (in terms of validity and practicality) Electronic Student Worksheets (E-Worksheet) based project using FlipHTML5 in light interference topic. E-Worksheet developed to stimulate student’s science process skills. This research used design and development research (DDR) which consisted of 4 stages, namely analysis, design, development, and evaluation. The results of the product validity were assessed by experts consisting of two high school physics teachers and a lecturer from the physics education department of the University of Lampung who got an average score of 3.56 with the very valid category. The E-Worksheet practicality in terms of the legibility, the student views that was completed by 9 students, and the teacher views that was completed by 5 high school physics teachers got an average percentage of 90% with the very practical category. These results showed that E-Worksheet were valid and very practical to stimulate student’s science process skills. Based on teacher views, the E-Worksheet is very possible to be implemented in online and face-to-face learning especially in the covid-19 pandemic era. The E-Worksheet can be used as multimedia to support online learning.